Pengaruh Pemahaman Investasi, Modal Minimal, Dan Motivasi Terhadap Minat Mahasiswa Dalam Melakukan Investasi Di Pasar Modal Syariah (Studi Mahasiswa Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Fatmawati Sukarno Bengkulu Angkatan 2020) - Olvy Renjani; Nurul Hak; Yetty Afrida Indra (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to: (1) find out how much influence understanding investment, minimum capital, and motivation has on students' interest in investing in the sharia capital market. (2) find out whether understanding investment, minimum capital, and motivation simultaneously have a significant effect on students' interest in investing in the Islamic capital market. Types of field research data with a quantitative approach. To reveal this problem in depth and comprehensively. This research uses an associative quantitative approach by collecting primary data in the form of a questionnaire distributed to 75 respondents. The data analysis technique used is multiple linear regression. The research results show that there is an influence of There is no influence of X2 on Y because the significant value is 0.493 > 0.05, so Ha is rejected, meaning there is no influence of minimum capital on students' interest in investing. There is an influence of The variables investment understanding, minimum capital, and motivation influence students' interest in investing in the Islamic capital market by 0.308 or 30%, while the remaining 70% is explained by other factors not examined in this research.